2018
DOI: 10.1161/circresaha.118.313225
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Mediated Gene Editing to Assess the Roles of Tet2 and Dnmt3a in Clonal Hematopoiesis and Cardiovascular Disease

Abstract: Experiments using lentivirus vector/CRISPR methodology provided evidence suggesting that inactivating DNMT3A mutations in hematopoietic cells contributes to cardiovascular disease. Comparative analyses showed that inactivation of Tet2 and Dnmt3 was similar in their ability to promote Ang II-induced cardiac dysfunction and renal fibrosis in mice. However, gene-specific actions were indicated by differences in kinetics of hematopoietic stem/progenitor cell expansion and different patterns of inflammatory gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
312
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(339 citation statements)
references
References 22 publications
22
312
0
5
Order By: Relevance
“…Murine experiments demonstrated that mice with TET2-deficient HSC had larger atherosclerotic plaques [51,52]. This association appeared to be causal, as TET-2 inactivation in macrophages enhanced their pro-inflammatory activity upon antigen stimulation, with increased production of pro-inflammatory molecules IL-1β [49,[51][52][53], IL-6 [49,[51][52][53], as well as that of single C-X-C motif (CXC) chemokines CXCL1 [51] (a neutrophil chemotactic factor), CXCL2 [51] (also known as macrophage inflammatory protein 2-alpha), CXCL3 [51] (also known as macrophage inflammatory protein-2-beta) and platelet factor 4 [51] (involved in coagulation). TET2 regulates the transcription of pro-inflammatory factors such as IL-6 by binding to their gene promoters; once bound, TET2 recruits histone deacetylase (HDAC2) at this level, thereby facilitating histone deacetylation that terminates gene transcription [54].…”
Section: The Interplay Of Chip Immune Dysregulation and Cardiovascumentioning
confidence: 95%
See 2 more Smart Citations
“…Murine experiments demonstrated that mice with TET2-deficient HSC had larger atherosclerotic plaques [51,52]. This association appeared to be causal, as TET-2 inactivation in macrophages enhanced their pro-inflammatory activity upon antigen stimulation, with increased production of pro-inflammatory molecules IL-1β [49,[51][52][53], IL-6 [49,[51][52][53], as well as that of single C-X-C motif (CXC) chemokines CXCL1 [51] (a neutrophil chemotactic factor), CXCL2 [51] (also known as macrophage inflammatory protein 2-alpha), CXCL3 [51] (also known as macrophage inflammatory protein-2-beta) and platelet factor 4 [51] (involved in coagulation). TET2 regulates the transcription of pro-inflammatory factors such as IL-6 by binding to their gene promoters; once bound, TET2 recruits histone deacetylase (HDAC2) at this level, thereby facilitating histone deacetylation that terminates gene transcription [54].…”
Section: The Interplay Of Chip Immune Dysregulation and Cardiovascumentioning
confidence: 95%
“…A detailed discussion of these is beyond the scope of this review, and the authors direct the reader to an excellent updated overview of these models [48]. Briefly, here we will discuss evidence obtained using two mice models of hypertension-induced HFpEF, provoked by salty drinking water, unilateral nephrectomy, and chronic exposure to aldosterone (SAUNA) for 30 days [9], or by continuous angiotensin II (AT II) infusions administered via mini-osmotic pumps for 4 weeks [49]. A third model recapitulates HFpEF associated with aging, as older and senescent C57BL/6 mice present with mild left ventricular hypertrophy (LVH), interstitial fibrosis and diastolic dysfunction, but without hypertension (HTN) [9].…”
Section: Animal Models Of Hfpefmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidently, study of additional CHIP subtypes may uncover further intricacies of how CHIP hazardously intersects with the leading comorbidities in the developed world. For example, CRISPR-Cas9−edited models of CH for both Tet2 and Dnmt3a mutations yield similar effects on cardiac function, yet Dnmt3a mutants undergo limited expansion and exhibit different cytokine expression, suggesting a different means of achieving the same severity of disease [56]. DNMT3A mutations may cause further dysfunction in the realm of immunity and respirology.…”
Section: Ch As a Consequence Of Inflammationmentioning
confidence: 99%
“…In this regard, TET2-deficiency results in an increased pro-inflammatory phenotype in murine macrophages, which may help to promote atherosclerosis (Abegunde, Buckstein, Wells, & Rauh, 2018;Cull, Snetsinger, Buckstein, Wells, & Rauh, 2017;Cull, Snetsinger, & Rauh, 2016). CH also alters cardiac repair by inflammatory pathways (Sano et al, 2018). Also in line with the inflammatory role of TET2, patients who underwent allogeneic bone marrow transplantation from donors with CH had an increased risk of chronic graft-versus-host disease (Frick et al, 2019).…”
Section: Introductionmentioning
confidence: 99%